Infecção do trato urinário causada por Escherichia coli uropatogênica resistente a antibióticos: um importante problema de saúde pública (Research, Society and Development, 2021)
Urinary tract infection (UTI) caused by uropathogenic Escherichia coli (UPEC) is one of the most prevalent bacterial infections and is a major cause of health-related morbidity and hospital costs worldwide. The rising bacterial resistance to routinely given antibiotics for infected individuals is becoming a significant source of concern. Current research shows that UPEC is becoming more resistant to multiple antibiotic classes, including fluoroquinolones, beta-lactams, and aminoglycosides, as a result of genetic determinants of resistance and multidrug-resistant clones. Knowledge of the local etiology and the sensitivity profile of the most common uropathogens to antibiotics should guide decisions in the empirical therapy of uncomplicated UTI. Given the high prevalence of UTI and multidrug-resistant bacteria, preventative measures such as the development of an efficient vaccination are essential. The current work is an integrated literature review that synthesizes information on UTIs caused by antibiotic-resistant uropathogenic E. coli and considers the practical implications of key research results.